Standard methods for Apis mellifera venom research - de Graaf, Dirk C.; Brochetto Braga, Márcia Regina [UNESP]; de Abreu, Rusleyd Maria Magalhães; Blank, Simon; Bridts, Chris H.; De Clerck, Luc S.; Devreese, Bart; Ebo, Didier G.; Ferris, Timothy J.; Hagendorens, Margo M.; Justo Jacomini, Débora Laís; Kanchev, Iliya; et al. (Taylor & Francis, 2020)
Honey bees have a sting which allows them to inject venomous substances into the body of an opponent or attacker. As the sting originates from a modified ovipositor, it only occurs in the female insect, and this is a defining feature of the bee species that belong to a subclade of the Hymenoptera called Aculeata. There is considerable interest in bee venom research, primarily because of an important subset of the human population who will develop a sometimes life threatening allergic response after a bee sting. However, the use of honey bee venom goes much further, with alleged healing properties in ancient therapies and recent research. The present paper aims to standardize selected methods for honey bee venom research. It covers different methods of venom collection, characterization and storage. Much attention was also addressed to the determination of the biological activity of the venom and its use in the context of biomedical research, more specifically venom allergy. Finally, the procedure for the assignment of new venom allergens has been presented. Las abejas melíferas tienen un aguijón que les permite inyectar sustancias venenosas en el cuerpo de un oponente o atacante. El aguijón es un ovipositor modificado que solo se manifiesta en el insecto hembra, siendo este una característica que define a las especies de abejas que pertenecen al subclado de himenópteros llamada Aculeata. Hay un interés considerable en la investigación del veneno de abeja, principalmente debido a que un porcentaje importante de la población humana desarrollará una respuesta alérgica - a veces mortal - a la picadura de abeja. Sin embargo, el uso del veneno de la abeja melífera abarca mucho más, con presuntas propiedades curativas en terapias antiguas e investigaciones recientes. El presente trabajo tiene como objetivo estandarizar métodos seleccionados para la investigación del veneno de las abejas melíferas. Cubre diferentes métodos de recolección, caracterización y almacenamiento de veneno. También se prestó mucha atención a la determinación de la actividad biológica del veneno y su uso en el contexto de la investigación biomédica, más específicamente la alergia al veneno. Finalmente, se ha presentado el procedimiento para la asignación de nuevos alérgenos de veneno.
Keywords: acid phosphatase; Apis mellifera; BEEBOOK; COLOSS; esterase; honey bee; hyaluronidase; phospholipase A2; sting allergy; venom characterization; venom collection; venom composition; venom storage